Analysis of The Impact and Dynamics of Gratification In The Practice of State Administrative Law - Irawan, Taufik; Yanto, Yanto (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2024)
The practice of gratification, which involves receiving rewards or gifts by state administrative officials, can undermine the foundations of good governance principles. The implications of gratification practices can damage the government's image, reduce public trust, and affect the effectiveness of public policy. This phenomenon creates challenges in various aspects, including public ethics, public trust, and the effectiveness of legal institutions. Apart from that, the dynamics of gratification can also penetrate the administrative decision-making process. Objective considerations in decision making can be disturbed by the influence of gratification, resulting in policies that are not in line with the public interest. This opens up gaps in inequality in public services and inefficient use of public resources. The high complexity of this problem requires an in-depth understanding of the dynamics of gratification in the practice of State Administrative Law. Especially solutions to overcome the problems of awareness and ethics of state administration administrators, internal and external supervision of perpetrators of gratification, environmental conditions of work organizations and active participation from various stakeholders to prevent and eradicate can involve various parties, especially law enforcement officials, the media and the public to proactively reveal , urge and report behavior that leads to gratification. This article explores the phenomenon of gratification in the context of state administrative law practice. Through in-depth analysis, we explain the dynamics behind gratification, its impact on the effectiveness of the state's administrative legal system, and efforts that can be made to overcome this problem. Our research concludes that a deep understanding of gratification is critical to enhancing the integrity and credibility of the country's administrative legal system.